Water quality, climatic factors and plant traits as predictors to the insect’s abundance in the paddy field / Norazliza Rosly - Rosly, Norazliza (2015)
Paddy (Oryza sativa L.) was cultivated in many countries. The major problem in paddy field is insect pests. Due to that, pesticides were widely used. However, heavily usage can cause environmental pollution, loss of non-target pests, insecticides resistance and residual toxicity. Therefore, beneficial insects should be used as an alternative method. Understanding habitat preferences and factors that can reflect populations of beneficial insects are urgently needed. Following that, the intention of this study is to assess the environmental factors that reflect the abundance of beneficial insects in the paddy field at Sungai Burong, Tanjung Karang, Selangor. A total of 1,257 individuals of insects consisted of five orders (Odonata, Hemiptera, Coleoptera, Lepidoptera and Diptera), two sub-orders (Anisoptera and Zygoptera) and six families (Gerridae, Coccinellidae, Staphylinidae, Pyralidae, Cicadellidae and Chironomidae) found throughout two cropping periods. The compositions and diversity of the insects varied throughout the sampling period. The species richness and evenness was highest during vegetative phase. Besides, according to Mann-U Whitney and Kruskal-Wallis Tests, most of insects were influenced by localities of sampling areas. There were significance indirect relationship of insects with water temperature, Biochemical Oxygen Demand and Chemical Oxygen Demand. The plant height, insect pests, temperature, rainfall and humidity were good predictors on abundance of beneficial insects however, the R2 values were relatively low due to significance indirectly relationship between water parameters with insects. Consideration of all factors, the total variance showed more than 78%, which indicate a strong correlation between those parameters insects in the paddy field.